2016
DOI: 10.1038/srep33904
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to HT-2 toxin causes oxidative stress induced apoptosis/autophagy in porcine oocytes

Abstract: T-2 toxin is a main type A trichothecene mycotoxin which is the most toxic trichothecence. T-2 toxin has posed various toxic effects on human and animals in vigorous cell proliferation tissues like lymphoid, hematopoietic and gastrointestinal tissues, while HT-2 toxin is the major metabolite which is deacetylated by T-2 toxin. In this study, we focused on the toxic effects of HT-2 on porcine oocyte maturation. We treated the porcine oocyte with HT-2 toxin in vitro, and we first found that HT-2 treatment inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 37 publications
4
32
0
Order By: Relevance
“…Contradictory results have been published concerning in vitro genotoxicity of mycotoxins (Takakura et al, ). In our assay, DON, NIV and HT‐2 induced γH2AX in HepG2 cells, consistent with the results of other in vitro genotoxicity studies that reported enhanced DNA damage and apoptosis by these mycotoxins, probably induced through oxidative stress (Zhang et al, ; ; Del Regno et al, ). In conclusion, the present study strongly supports the genotoxicity of some individual chemicals present in the tested mixtures already reported in the literature.…”
Section: Discussionsupporting
confidence: 91%
“…Contradictory results have been published concerning in vitro genotoxicity of mycotoxins (Takakura et al, ). In our assay, DON, NIV and HT‐2 induced γH2AX in HepG2 cells, consistent with the results of other in vitro genotoxicity studies that reported enhanced DNA damage and apoptosis by these mycotoxins, probably induced through oxidative stress (Zhang et al, ; ; Del Regno et al, ). In conclusion, the present study strongly supports the genotoxicity of some individual chemicals present in the tested mixtures already reported in the literature.…”
Section: Discussionsupporting
confidence: 91%
“…However, little data are involved in the effects of OTA on autophagy in pigs. The present study showed that dietary supplementation of OTA increased autophgay‐related gene Atg5 and LC3 II expression in kidney and spleen, consistent with previous studies about other mycotoxin that AFB1 or DON or HT2 could induce Atg5 and LC3 II expression in macrophages or in porcine intestinal cells or in porcine oocytes …”
Section: Discussionsupporting
confidence: 92%
“…The present study showed that dietary supplementation of OTA increased autophgayrelated gene Atg5 and LC3 II expression in kidney and spleen, consistent with previous studies about other mycotoxin that AFB1 or DON or HT2 could induce Atg5 and LC3 II expression in macrophages 45 or in porcine intestinal cells 20 or in porcine oocytes. 46 In conclusion, this study verified the nephrotoxicity and immuno- OTA and ER stress, p38, and ERK1/2 MAPK signaling pathway and autophagy in pigs.…”
Section: Discussionsupporting
confidence: 61%
“…In a study on the apoptosis mechanism in liver cells induced by T-2 toxin [21], it was also found that p53 was up-regulated under T-2 toxin stress, which implied that the effect of T-2 toxin on cells was apoptosis rather than necrosis, and it was probably induced through the mitochondrial pathway. The induction of apoptosis of T-2 toxin through a possible mechanism involving reactive oxygen species-mediated mitochondrial pathway is also supported by other authors [13].…”
Section: Discussionmentioning
confidence: 97%
“…fungus can induce apoptosis -a programmed cell death -of several cell lines of humans and animals [22]. Since T-2 toxin is a main type A trichothecene mycotoxin which is the most toxic trichothecence, it has posed various toxic effects on humans and animals in vigorous cell proliferation tissues like lymphoid, hematopoietic and gastrointestinal tissues [9,21]. Simultaneously, T-2 toxin is one of the most important trichothecene mycotoxins which occurs in various agricultural products [20] causing severe diseases among humans and animals, which can even lead to death [12].…”
Section: Introductionmentioning
confidence: 99%